Ecological and Social Aspects in The Managementof Post-Mining Areas. an Example of the Adamów Lignite Basin = Ekologiczne i społeczne aspekty w zarządzaniu obszarami pogórniczymi. Przykład Adamowskiego Zagłębia Węgla Brunatnego - Fagiewicz, Katarzyna; Mękarski, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The study presents a management model for post-mining areas, which includes the process of reclamation and management in the context of the socio-ecological system. This means that it is necessary to include the relations in the management system that occur between the main stakeholders (internal relations) and the ecological, economic and socio-cultural conditions of the environment (external relations).
Keywords: social-ecological system; post-mining areas; revitalization; environmental management; system społeczno-ekologiczny; obszary pogórnicze; rewitalizacja; zarządzanie środowiskowe